Analytical Study of Some Start Phase Kinematical Variables and Their Relation to Archiving 50m Freestyle for National League Swimmers Aged 13 – 15 Years Old - Hashim , Ahmed; Thamir , Ahmed (Journal of Physical Education, 2023)
Trainers and swimmers continue searching for the best way to develop the swimmers’ achievement in general and numbers in world champions in particular. Since biomechanical variables have an integral role on the improvement of swimmer’s level of achievement, the researchers aim at identifying the values of some biomechanical variables of start phase and achievement as well as identifying the relation between these variables and achieving 50m swimming. They used the descriptive method by shooting one test for biomechanical variables and achieving 50 m swimming. The data was treated using proper statistical operations to conclude that pushing force and launch speed affect the development and improvement of achievement. The researchers recommended making similar studies paying attention to effective variables on 50m swimming.